Driving personalized medicine: capturing maximum net present value and optimal return on investment. (January 2010) - Roth, Mollie; Keeling, Peter; Smart, Dave
In order for personalized medicine to meet its potential future promise, a closer focus on the work being carried out today and the foundation it will provide for that future is imperative. While big picture perspectives of this still nascent shift in the drug-development process are important, it is more important that today''s work on the first wave of targeted therapies is used to build specific benchmarking and financial models against which further such therapies may be more effectively developed. Today''s drug-development teams need a robust tool to identify the exact drivers that will ensure the successful launch and rapid adoption of targeted therapies, and financial metrics to determine the appropriate resource levels to power those drivers. This special report will describe one such benchmarking and financial model that is specifically designed for the personalized medicine field and will explain how the use of this or similar models can help to capture the maximum net present value of targeted therapies and help to realize optimal return on investment.